A Study on Computerized Accounting Practices of Small Business in Thanjavur District - Surulipal, Mr.T.; Baranidharan, Dr.K. (IJRDO - Journal of Business Management, 2018)
In a dynamic world, the availability and adoption of Information and Communication Technologies (ICTs) across the globe has altered the norm of the game and expectations of the new mode of economics activities. The norm of inter and transnational trading changed dramatically to admit the increasing number of financial transactions and trade-related activities that take place via the Internet and technologically assisted tools. The traditional view of small business record keeping suggest that it is a paper based and hand of to the accountant firm to prepare the annual tax return. Porter & Millar (1985) mentioned in this competitive advantage, over the years, information technology had played a major role, changing the nature of business who knows its effects. With the introduction of new technology and more user friendly software, computerized accounting system (CAS) appears to reduce the problems in book record keeping practice. Furthermore, with the new and rapid financial information, new updates and changes will be available for others in making decisions.Accounting plays a critical role in the success or failure of contemporary business institutions. Accounting systems are responsible for recording, analyzing, monitoring and evaluating the financial condition of companies, preparation of documents necessary for tax purposes, providing information support to many others organizational functions. Accounting systems provide a source of information to owners and managers of SMEs operating in any industry for the use in measuring financial performance. There are 566 Small and medium enterprises in Tanjavoor. Most of the enterprises are very small and some are medium. Establishment of SMEs in research area is increasing day by day.